The Law of Trading at the Mid of the Friday Praying - Ibnu Muhdir (EkBis: Jurnal Ekonomi dan Bisnis, 2021)
This paper discusses the law of trading (buying and selling) at the time of Friday prayings. This discussion has not developed since classical scholars. Allah forbids buying and selling at the time of Friday prayings. The scholars are of the opinion that the law of buying and selling at the time of Friday prayings is haraam, because they always associate it with the law of Friday prayings. According to them, the law of Friday praying is obligatory. The author performs re-ijtihad against the law of buying and selling at the time of Friday prayings. By using the ijtihad method bayāni, the author concludes that the prohibition on buying and selling at the time of Friday prayings is only limited to the etiquette or ethics case. It is associated with the law of Friday prayings which according to the author, it is sunnah. For this reason, the author stipulates that the law of buying and selling at the time of Friday prayings is makruh (disliked).